Sistem Diagnosis Penyakit Pada Sapi Potong Menggunakan Metode Bayesian Network - Greviko Bayu Kristi; Nurul Hidayat; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Cattle are animals that have a lot of economic potential. Diseases of cattle can be spread quickly, and can make the cattle dead. Diseases of cattle can be caused by bacteria, viruses, fungi, and parasites. To prevent diseases of cattle is not continues, the farmers of cattle must know about diseases in animal cow, so it can do the prevention and treatment as early as possible. To diagnosis which diseases that attack cattle, it is necessary to build an diagnosis systems. This diagnosis on diseases of cattle is using Bayesian Network method. The diagnosis process is done by entering the facts of the symptoms on cattle and then calculated by using Bayesian Network. The result of this system is the diagnosis of diseases that attack the cattle with the recommendation of its control solution. Based on the results of the test that coducted in this study resulted an accuracy of 93.33%, so it can be concluded this expert system to diagnosis diseases on cattle using Bayesian Network is able to work well.